Psoriasis as a Predictor of Cardiometabolic Comorbidity in Women: A Study Based on the Danish National Birth Cohort - Christoffer Blegvad; Anne-Marie Nybo Andersen; Abdulfatah Adam; Claus Zachariae; Lone Skov (Medical Journals Sweden, 2018)
Psoriasis is associated with cardiometabolic comorbidity; however, whether this is due to common lifestyle-related risk factors is unclear. This study investigated the association between psoriasis and cardiometabolic comorbidity, taking body mass index and smoking into account. The population comprised expectant mothers in the Danish National Birth Cohort (established 1996-2002). During pregnancy, the women were asked about physician-diagnosed psoriasis. Any association with self-reported cardiometabolic comorbidity 11 years later was assessed using logistic regression. The cohort was also followed up for hospital-diagnosed comorbidity, including cardiac death, until 31 December 2014, and the risk was assessed using Cox regression. A total of 2,435 women with psoriasis (2.90%) and 81,388 women without were identified. Psoriasis was significantly associated with self-reported hypercholesterolaemia (adjusted odds ratio 1.31; 1.01-1.70) and hospital-diagnosed hypertension (adjusted hazard ratio 1.33; 1.08-1.65). Women with psoriasis have an increased risk of developing cardiometabolic comorbidity in early adult life.